SELF – ESTEEM PADA PENGGUNA SECOND ACCOUNT INSTAGRAM - Dhiva Chantyca; Mochamad Widjanarko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores how the use of second accounts on the Instagram platform influences the development of self-esteem among adolescents. The aim of this research is to analyze the dynamics of self-esteem dimensions in second account users. This study employs a qualitative method with a phenomenological approach, involving three informants who have used second accounts for more than two years. Data were collected through interviews and analyzed using coding techniques and data triangulation. The results show that all three informants feel more comfortable and confident using their second accounts due to the safe space they provide, free from social pressure. The informants are able to express their emotions, opinions, and reveal personal sides that they cannot display on their main accounts. Differences were found in how each informant deals with criticism and builds self- acceptance; however, in general, the use of second accounts helps reduce feelings of insecurity and enhances their sense of self-worth.